2018
DOI: 10.1007/s11010-018-3284-1
|View full text |Cite
|
Sign up to set email alerts
|

The biological changes of umbilical cord mesenchymal stem cells in inflammatory environment induced by different cytokines

Abstract: Mesenchymal stem cells (MSCs) are used as therapeutic tool for the treatment of immune diseases. The inflammatory environment also influences the characteristics of MSCs after transplantation. The aim of the study was to investigate the effects of pro-inflammatory cytokines on the characteristics of umbilical cord mesenchymal stem cells (UCMSCs). UCMSCs were exposed to pro-inflammatory cytokines in vitro for 3 and 7 days, and the biological properties were analyzed. The results showed that the proliferation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Several authors have noted an increase in the antigen-presenting properties of MSCs as a result of IFN-γ pretreatment [72]. Other studies have shown that the "priming" of MSCs in vitro with IFN-γ, TNF-α, or IL-1β leads to the formation of the immunosuppressive phenotype MSC-2 [47,73,74]. Our results showed, for the first time, that after administration in mice, modified MSCs treated with IFN-γ cause a pronounced (tenfold) decrease in the cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have noted an increase in the antigen-presenting properties of MSCs as a result of IFN-γ pretreatment [72]. Other studies have shown that the "priming" of MSCs in vitro with IFN-γ, TNF-α, or IL-1β leads to the formation of the immunosuppressive phenotype MSC-2 [47,73,74]. Our results showed, for the first time, that after administration in mice, modified MSCs treated with IFN-γ cause a pronounced (tenfold) decrease in the cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects of IL-1β priming on MSCs proliferation and differentiation, heterogeneous results have been reported (Figure 1 ). Namely, while IL-1β preconditioning increases equine AT-MSCs and human synovium-derived MSCs proliferation[ 65 , 66 ], exposure of UC-MSCs to IL-1β results in suppressed proliferation[ 67 ]. Moreover, functional analyses of human BM-MSCs have revealed that treatment with IL-1β does not affect the proliferation of these cells, and promotes their migration and adhesion to extracellular matrix components[ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sonomoto et al[ 70 ] demonstrated the ability of IL-1β to induce the osteogenic differentiation of human BM-MSCs via the Wnt pathway. Increased osteogenesis has also been found for equine AT-MSCs and human UC-MSCs treated with IL-1β[ 65 , 67 ]. On the other hand, depending on the concentration, IL-1β exerts dual effects on the osteogenesis of periodontal ligament-MSCs, since low doses of IL-1β promote osteogenesis by activating the bone morphogenetic protein (referred to as BMP)/Smad signaling pathway, while higher doses of the cytokine impede osteogenesis[ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under in vitro conditions, repetitive passaging [2], and endogenous reactive oxygen species (ROS) and DNA damage [5] are associated with stem cell senescence. Moreover, the presence of an inflammatory microenvironment both in vitro or in vivo can induce cellular senescence [6]. On the other hand, a hypoxic condition has shown to preserve stem cell integrity in long‐term cultures [7].…”
Section: Introductionmentioning
confidence: 99%